1980
DOI: 10.1176/ajp.137.6.683
|View full text |Cite
|
Sign up to set email alerts
|

Self-perception and academic achievement: variations in a desegregated setting

Abstract: The author studied 101 black and 412 white fifth-grade students and found no significant racial differences on any measures of general or area-specific (i.e., school, peers, home) self-esteem when socioeconomic status (SES) was controlled but found significant differences by SES on most measures when race was controlled. There was a positive correlation between self-concept of ability and SES when race was controlled, but when SES was controlled black children scored significantly higher than did white childre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

1984
1984
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(5 citation statements)
references
References 12 publications
0
3
0
2
Order By: Relevance
“…Because academic achievement and academic self-esteem are positively related (Hansford & Hattie, 1982; Skaalvik & Hagtvet, 1990), we would expect higher academic self-esteem for White students. Although some contradictory results have been reported (see, e.g., Hare, 1980; Kugle, Clements, & Powell, 1983), several investigators have found support for this expectation (see, e.g., Lay & Wakstein, 1985; Mboya, 1988; W. L. Osborne & LeGette, 1982; Richman et al, 1985).…”
Section: Racial Differences In Self-esteemmentioning
confidence: 99%
“…Because academic achievement and academic self-esteem are positively related (Hansford & Hattie, 1982; Skaalvik & Hagtvet, 1990), we would expect higher academic self-esteem for White students. Although some contradictory results have been reported (see, e.g., Hare, 1980; Kugle, Clements, & Powell, 1983), several investigators have found support for this expectation (see, e.g., Lay & Wakstein, 1985; Mboya, 1988; W. L. Osborne & LeGette, 1982; Richman et al, 1985).…”
Section: Racial Differences In Self-esteemmentioning
confidence: 99%
“…Middle-SES blacks often have been ignored altogether in previous research because many studies erroneously compare low-SES blacks and middle-SES whites on the variables of interest (e.g., DuCette & Wolk, 1972). When a middle-SES group has been included, investigators typically have highlighted a deviant pattern of responding among disadvantaged blacks while stressing the similarities between middle-SES whites and blacks (e.g., Hare, 1980;Havighurst, 1976). The overall message from studies of this type is that socioeconomic class is a more important factor than race in determining black-white differences in motivation, and that when SES is controlled, racial differences disappear (also see Yando, Seitz, & Zigler, 1979).…”
Section: Race and Class Effectsmentioning
confidence: 99%
“…En el apartado de hallazgos obvios, esperables, conformes a las expectativas (cf., Gimeno, 1976;Hare, 1980) está que la autoestima (PH), sobre todo la escolar, aparece positivamente asociada con las calificaciones y con un nivel de aspiración que se refería a tareas semejantes a las escolares.…”
Section: Discussionunclassified
“…Tópicamente se considera que la autoestima o autoconcepto evaluativo se relaciona con la percepción de la propia competencia (Novick, Cauce y Grove, 1996), con el logro y el éxito (Mruk, 1995), con el rendimiento en el trabajo (Judge, Erez y Bono, 1998), con la amplitud y variedad de intereses vocacionales (Mullis y Mullis, 1997) y desde luego con el rendimiento escolar (Aunola, Stattin y Nurmi, 2000;Gimeno, 1976;Hare, 1980;Leondari, Syngollitou y Kiosseoglou, 1998). Es más, a autoconcepto y autoestima se les suele atribuir un papel mediador respecto a los logros académicos (Rogers, 1987, cap.…”
unclassified